Integrative systemic and family therapy for social anxiety disorder: manual and practice in a pilot randomized controlled trial (SOPHO-CBT/ST) - Hunger-Schoppe, Christina; Schweitzer, Jochen; Hilzinger, Rebecca; Krempel, Laura; Deußer, Laura; Sander, Anja; Bents, Hinrich; Mander, Johannes; Lieb, Hans (Frontiers in psychology, 2022)
Social anxiety disorders (SAD) are among the most prevalent mental disorders (lifetime prevalence: 7-12%), with high impact on the life of an affected social system and its individual social system members. We developed a manualized disorder-specific integrative systemic and family therapy (ISFT) for SAD, and evaluated its feasibility in a pilot randomized controlled trial (RCT). The ISFT is inspired by Helm Stierlin’s concept of related individuation developed during the early 1980s, which has since continued to be refined. It integrates solution-focused language, social network diagnostics, and genogram work, as well as resource- and problem orientation for both case conceptualization and therapy planning. Post-Milan symptom prescription to fluidize the presented symptoms is one of the core interventions in the ISFT. Theoretically, the IFST is grounded in radical constructivism and “Cybern-Ethics,” multi-directional partiality, and a both/and attitude toward a disorder-specific vs. non-disorder-specific therapy approach. SAD is understood from the viewpoint of social systems theory, especially in adaptation to a socio-psycho-biological explanatory model of social anxiety.